Online Shopping in the Hadith of al-Kulayni: A Study of Shi’i Muʿamalah - May Shinta Retnowati; Mohammad Ghozali; Mohammad Syifa urrosyidin (LPPM UIN Syekh Wasil Kediri, 2026)
Muslims do not only use hadith as evidence in the source of Islamic law but also make it an inseparable thing in istidlal in believing in the canonical and authoritative text of the Qur'an. The Shia group accepts the source of hadith originating from their group, according to them hadith not only includes all the sayings and behavior of the Prophet Muhammad, SAW, but also includes the sayings and behavior of the Ma'sum Imams. The existence of hadith views from the Shiite group requires a detailed study of hadith science from hadith experts. The Shiite group takes hadith from books that they consider authentic, such as one of them is the book Al Kafi by Abu Ja'far Muhammad ibn Yaqub ibn Ishaq al Kulaini al Razi. This book is used by the Shia group as a source of religious needs that include religious sciences and practical law in accordance with strong hadith from the actual source on legal science in the maaliyah activities of the Shia group regarding the development of online shopping so that the aim is to get a comprehensive view of contemporary muamalah activities (online shopping) reviewed in the book of al Kafi as the legal basis for hadith for the Shia group so that it will increase scientific insight in the field of hadith science. The methodology used is Literature review. With today's technological advances, long-distance buying and selling has become the norm in the business world, or what is known as online shopping. In the book of al kafi, the practice of online buying and selling can be done as long as first it has the value of worship, second, the personality is integrated, third, halal wealth